Building a culture of accountability in service delivery: an overview of results of the GDN project on Varieties of Governance in Service Delivery (2013)
This paper summarizes the results of a Global Development Network study, carried on by sixteen multidisciplinary research teams and covering thirty developing countries, under the authors general direction, on the effects of different governance structures on the quality and equity of access in three public services: basic education, drinking water supply and roads. Governance reforms analyzed referred mostly to decentralization, formal processes of citizen's participation and alternative modes of delivery and, within each of them, emphasis was placed on the effects of accountability systems, informational flows and incentive structures. Case studies used both econometric techniques and qualitative analysis based on surveys and structured interviews of policy makers, service providers and users. The impact of governance reforms and alternatives was found to vary significantly with country context, but three major conclusions emerged: 1) Political culture and legacy are the deeper determinants of effective accountability and results. Thus, countries with a history of highly centralized and authoritarian regimes find it harder to make decentralization, participation and competitive modes of delivery work effectively. However, a culture of accountability can be built overtime when adequate institutions and incentives are introduced and maintained overtime; 2) Adequate information flows are not only a necessary condition, but they often promote effective accountability and better results, as they lead citizens and clients to demand accountability and agents to be more responsive to user needs; 3) Self-financing schemes also promote more accountability and better results, as users demand better services when they pay for them and citizens are more demanding (and local authorities are more responsive to their needs) when local taxes finance local services.